Gambaran Klinis dan Laboratorium Kejadian Resistensi Karbapenem Bakteri Acinetobacter Baumannii - Muhammad Cendekia Robbani; Usep Abdullah Husin; Winni Maharani Mauliani (Jurnal Riset Kedokteran, 2025)
Abstract. Antimicrobial Resistance Collaborators mentioned there are six main pathogens in antibiotic resistance cases, including Acinetobacter baumannii. This study aims to determine the incidence, clinical features and laboratory results of carbapenem-resistant Acinetobacter baumannii infection. The sampling method used total sampling and was carried out in November-December 2024 at Al-Ihsan Hospital, from all patients with Acinetobacter baumannii findings, most patients were obtained according to the inclusion and exclusion criteria. The results showed that the majority of patients were female, with the most age group being infants aged less than one year, and the most sampling locations were in the ICU. Most clinical features were sepsis accompanied by respiratory distress. The main sample type used was blood. Most of the antibiotics tested showed no response in the culture. It was found that most of the Carbapenem Resistant Acinetobacter baumannii (CRAB) cultures showed extensively-drug resistant (XDR) characteristics, while the rest showed multi-drug resistant (MDR) characteristics. Some findings are not in line with previous studies that have been carried out due to the limited number of patients. Based on the results of the national antibiotic sensitivity examination, there are similarities in the resistance patterns of the study with the 2023 surveillance. Abstrak. Antimicrobial Resistance Collaborators menyebutkan terdapat enam patogen utama dalam kasus resistensi antibiotik, diantaranya Acinetobacter baumannii. Penelitian ini bertujuan untuk mengetahui insidensi, gambaran klinis dan hasil laboratorium infeksi Acinetobacter baumannii yang resisten terhadap karbapenem. Metode pengambilan sampel menggunakan total sampling dan dilakukan pada bulan November—Desember 2024 di RSUD Al-Ihsan, dari seluruh pasien dengan temuan Acinetobacter baumannii didapatkan sebagian besar pasien sesuai dengan kriteria inklusi dan eksklusi. Hasil penelitian menunjukkan bahwa mayoritas pasien berjenis kelamin perempuan, dengan kelompok usia terbanyak adalah bayi berusia kurang dari satu tahun, dan lokasi pengambilan sampel terbanyak berada di ICU. Gambaran klinis terbanyak berupa sepsis disertai gangguan pernafasan. Jenis sampel utama yang digunakan adalah darah. Sebagian besar antibiotik yang diujikan tidak menunjukkan respons pada biakkan. Ditemukan bahwa sebagian besar biakkan Carbapenem Resistant Acinetobacter baumannii (CRAB) menunjukkan karakteristik extensively-drug resistant (XDR), sementara sisanya menunjukkan karakteristik multi-drug resistant (MDR). Beberapa hasil temuan tidak sejalan dengan penelitian terdahulu yang telah dilaksanakan karena jumlah pasien yang terbatas. Berdasarkan hasil pemeriksaan kepekaan antibiotik nasional, terdapat kesamaan pola resistensi penelitian dengan surveilans tahun 2023.